Chromium bioaccumulation, oxidative stress metabolism and oil content in lemon grass Cymbopogon flexuosus (Nees ex Steud.) W. Watson grown in chromium rich over burden soil of Sukinda chromite mine, India. (March 2019) - Patra, Deepak Kumar; Pradhan, Chinmay; Patra, Hemanta Kumar
Abstract: Lemon grass plants grown in Cr rich over burden soil of Sukinda chromite mine (India) countered Cr toxicity and oxidative stress with the production of reactive oxygen species and induced antioxidative defense system. Varied percentage of Cr rich over burden soil was applied to lemon grass pants to evaluate the actions of oxidative inhibitors enzymes extracted and assayed from both roots and shoots. The study also assessed the oil content and its composition in response to the different percentage of Cr available in over burden soil. In order to evaluate the defense system of a plant against oxidative stress and determine the level of reactive oxygen species, the experiments were undertaken in the presence and absence of Cr in soils. The results indicated that the action of oxidative inhibitor enzymes increased significantly in roots as compared to shoots with increasing concentration of Cr in overburden soil. Higher concentration of Cr in soils inhibited the enzyme activity both in roots and shoots. The level of ROS in plants also enhanced with the increase in the concentration of Cr in the soil. In order to control the oxidative damage in plants, lemon grass can be considered defensive in nature to build up the antioxidant system which can scavenge the reactive oxygen species (ROS). Highlights: Lemon grass has antioxidative defense system to cope up with oxidative damage induced by Cr. Oil, Citral-a, and Citral-b content of lemon grass leave increased with increase in the soil chromium concentration up to a certain limit. The level of reactive oxygen species (ROS) in plants also enhanced with rise in the concentration of chromium in soil. The lemon grass plants can propagate in Cr rich over burden soil without significant negative effects on plant growth and oil quality and quantity. The fibrous root system of lemon grass plants helps for bioaccumulation of Cr from contaminated soils through its rhizofiltration activity.